Etude comparative de l'effet du semis direct et du labour conventionnel sur le comportement d'une culture de blé dur - Abdellaoui Z.; Fettih S.; Zaghouane O. (Troisièmes rencontres méditerranéennes du semis direct, 2006)
First results of a comparative study of zero, conventional and minimum tillage show that wheat crop responded better to conventional tillage. A considerable evolution of parasitism in terms of high weed infestation and disease development, namely the take-all, has been observed with a zero tillage trial. However, zero tillage has increased the water conservation capacity in the soil.
3. Mediterranean Meeting on no Tillage, 2006/03/23-25, Zaragoza (Spain)